Functional Dissection of Protein Kinases in Sexual Development and Female Receptivity of Drosophila - Chen, Jiangtao; Zhu, Huan; Wang, Rong; Su, Xiangbin; Ruan, Zongcai; Pan, Yufeng; Peng, Qionglin (Frontiers in Cell and Developmental Biology, 2022)
Protein phosphorylation is crucial for a variety of biological functions, but how it is involved in sexual development and behavior is rarely known. In this study, we performed a screen of RNA interference targeting 177 protein kinases in Drosophila and identified 13 kinases involved in sexual development in one or both sexes. We further identified that PKA and CASK promote female sexual behavior while not affecting female differentiation. Knocking down PKA or CASK in about five pairs of pC1 neurons in the central brain affects the fine projection but not cell number of these pC1 neurons and reduces virgin female receptivity. We also found that PKA and CASK signaling is required acutely during adulthood to promote female sexual behavior. These results reveal candidate kinases required for sexual development and behaviors and provide insights into how kinases would regulate neuronal development and physiology to fine tune the robustness of sexual behaviors.